Prioritization of Reputation Loss Factors Imposed By Pipeline Failure Subject to Corrosion - Libriati Zardasti; Norhazilan Md. Noor; Nordin Yahaya (Institut Teknologi Sepuluh Nopember, 2017)
Reputation loss of a pipeline failure subject to corrosion is commonly neglected due to its qualitative nature. However, case studies found that perceptions of the stakeholders are prone to affect pipeline owner’s long-term reputation. Identifying the influence factors is insufficient to assist the owner to respond if pipeline failure occurs. Thus, this article endeavors to prioritize the influential reputation loss factors by interviewing six experts of pipeline integrity management personnel. The analytic hierarchy process multi-criteria decision making method was selected to help the prioritization process. Result shows that the most influenced factor is the loss of customer confidence (B1) and employee(s) caused accident (C9) ranked the least. The effort to quantify reputation loss can be substituted by prioritizing them according to stakeholders’ preferences as an initial step to monetarily quantify these factors in future. Thus, a comprehensive pipeline risk assessment and the pipeline integrity management can be achieved and simultaneously improve the company’s annual profit margin.